2018
DOI: 10.1007/s10900-018-0502-4
|View full text |Cite
|
Sign up to set email alerts
|

Policy Implications and Research Recommendations: A Review of Hookah Use Among US College Students

Abstract: The rate of Hookah use among college students during the last decade is about 30%. Although college students perceive hookah use as a safer alternative to conventional cigarettes, hookah use increases the risk of disease and nicotine dependence, and therefore remains an area of concern. Presently, the US Food and Drug Administration (FDA) has little regulation for the manufacture, distribution, or sale of hookah. This review attempts to assess empirical literature relating to hookah use while focusing on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Students perceive waterpipe use as a safer alternative to conventional cigarettes [ 21 ]. In addition, few public health messages target the population with anti-waterpipe messages.…”
Section: Discussionmentioning
confidence: 99%
“…Students perceive waterpipe use as a safer alternative to conventional cigarettes [ 21 ]. In addition, few public health messages target the population with anti-waterpipe messages.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition to nicotine exposure, hookah users are exposed to carbon monoxide, oxidants, heavy metals, and phenols, which can lead to increased heart rate and blood pressure, impaired pulmonary function, nicotine dependence, chronic bronchitis, emphysema, and coronary artery disease. 22,23 The decreased oxygen deliverance has effects that expand more broadly with animal models, suggesting an increased likelihood of low birth weight, neonatal death, and growth restriction. 24 Studies have also demonstrated a greater risk of altered fetal autonomic cardiac regulation and nicotine withdrawal in neonates born to individuals who used electronic nicotine delivery systems during pregnancy.…”
Section: Background Tobacco Use and Smoking Terminologymentioning
confidence: 99%
“…Data from animal models have shown that nicotine intake in any form can cross the placenta and adversely affects fetal lung development 21 . In addition to nicotine exposure, hookah users are exposed to carbon monoxide, oxidants, heavy metals, and phenols, which can lead to increased heart rate and blood pressure, impaired pulmonary function, nicotine dependence, chronic bronchitis, emphysema, and coronary artery disease 22,23 …”
Section: Introductionmentioning
confidence: 99%